Corneal and Epithelial Thickness Mapping: Comparison of Enhanced Spectral-Domain- and Spectral-Domain-Optical Coherence Tomography. (5th October 2021) - Georgeon, Cristina; Marciano, Ilanite; Cuyaubère, Roxane; Sandali, Otman; Bouheraoua, Nacim; Borderie, Vincent
Abstract : Objective . To compare the results and repeatability of the corneal thickness (CT) and epithelial thickness (ET) maps provided by Enhanced Spectral-Domain-Optical Coherence Tomography with those of Spectral-Domain-OCT in normal eyes. Methods . 30 normal eyes of 30 patients were assessed by 3 trained operators with ESD-OCT and SD-OCT. Results . The central and minimum ET obtained with both devices were correlated: central ET, r  = 0.86, p < 0.05 ; minimum ET, r  = 0.72, p < 0.05 . Compared with SD-OCT, ESD-OCT tended to underestimate these figures by 1.4 and 1.9  μ m on average. The central and minimum CT obtained with both devices were strongly correlated: central CT, r  = 0.994, p < 0.05 ; minimum CT, r  = 0.995, p < 0.05 . ESD-OCT tended to overestimate these figures by 11 and 14  μ m on average. Repeatability was good for both devices with a mean coefficient of variation of measurements <6% for ET and <2% for CT. Interoperator variability (standard deviation and COV) was significantly higher for ESD-OCT than for SD-OCT for all local epithelial thicknesses and significantly lower for the central CT and several local corneal thicknesses, whereas no significant differences between both technologies were found for the central and minimum ET and the minimum CT. Conclusion . ESD-OCT and SD-OCT provide reproducible measurements of CT and ET in normal corneas with a strong correlation between both technologies. However, both technologies are not interchangeable when the main thickness parameters (i.e., central and minimum CT and minimum ET) are used for diagnosing early keratoconus or calculating the expected residual stromal bed thickness before corneal refractive surgery or anterior lamellar keratoplasty.